2018
DOI: 10.1002/biot.201800352
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Omics Study on the Impact of Cysteine Feed Level on Cell Viability and mAb Production in a CHO Bioprocess

Abstract: There is continual demand to maximize CHO cell culture productivity of a biotherapeutic while maintaining product quality. In this study, a comprehensive multi‐omics analysis is performed to investigate the cellular response to the level of dosing of the amino acid cysteine (Cys) in the production of a monoclonal antibody (mAb). When Cys feed levels are insufficient, there is a significant decrease in protein titer. Multi‐omics (metabolomics and proteomics, with support from RNAseq) is performed over the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 60 publications
4
47
0
Order By: Relevance
“…Tyrosine is a fluorescent molecule and therefore variants of this amino acids directly affect the fluorescent signals. Taurine can play an important role for antioxidant processes in cell cultivations . It is capable of building stable complexes with Cu 2+ and therefore might affect tryptophan fluorescence in a similar way as described for methionine .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyrosine is a fluorescent molecule and therefore variants of this amino acids directly affect the fluorescent signals. Taurine can play an important role for antioxidant processes in cell cultivations . It is capable of building stable complexes with Cu 2+ and therefore might affect tryptophan fluorescence in a similar way as described for methionine .…”
Section: Resultsmentioning
confidence: 99%
“…Through the coded factors out of the DoE it could be revealed that the derived, cell line dependent, models for specific lactate production q lac (cell line B), product titer (cell line A), and average specific cell growth µ average (cell line A) were mostly affected by the storage time and not by the preparation parameters of the P‐media. Although strong effects on the chemical media composition could be observed already after the media preparation processes (Table ) and the fact that several compounds have been reported before to have an impact on cell culture performance , potential effects of the media preparation parameters might have been masked by media storage or media equilibration conditions prior to inoculation. The impact of variable F‐media preparation parameters on process performance was negligible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple technique was also developed to screen multiple CHO cell clones for cell growth rate and protein production (Beketova et al, 2019). Additionally, a multi-omics study was carried out on the impact of cysteine feed level on cell viability and IgG 1 mAb production in 5 l bioreactors using CHO cells so as to obtain an in-depth understanding of the CHO cell biology (Ali et al, 2019). In a recent study, CHO cells were engineered with synthetic genetic circuits to tune the N-glycosylation of a stably expressed IgG (Chang et al, 2019).…”
Section: Mammalian Cellsmentioning
confidence: 99%
“…In a recent study, it was shown that a decrease of cysteine supply led to a depletion of glutathione (Ali et al, 2019). As a consequence, the oxidative stress generated led to cell death, titer decrease and differential expression of proteins.…”
Section: Discussionmentioning
confidence: 99%